Difunctional CoCu catalyst, preparation method thereof and application of difunctional CoCu catalyst in production of sulfur and ammonia
By synthesizing Cu-doped CoOOH dual-function electrocatalyst on foam cobalt, the problems of high energy consumption and secondary pollution of sulfur and nitrate pollutants in wastewater in the prior art are solved, and efficient NO3RR and SOR reactions are achieved, achieving Low energy consumption pollutant removal and resource recycling effects.
Patent Information
- Application Number
- CN202411206441.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-31
AI Technical Summary
When treating sulfur and nitrate pollutants in wastewater, the traditional method consumes high energy and is prone to secondary pollution. It lacks dual-function electrocatalysts that can efficiently catalyze NO3RR and SOR at the same time, making it difficult to achieve efficient and simple pollution. Material processing and resource recycling.
Synthesizing Cu-doped CoOOH dual-function electrocatalyst on foamed cobalt (CF) by in-situ growth method, used for cathode NO3RR and anode SOR, achieving efficient catalytic reduction of NO3 to NH3 and S2-oxidation to S at low potential and reduce energy consumption by electrochemical coupling method.
Achieved a current density of 100 mAcm-2 at low potential of 0.29 V (vs. RHE) and a 96% ammonia Faraday efficiency at -1.5 V (vs. RHE), reducing the energy consumption of the electrochemical reaction and successfully extracted High value-added products NH4Cl and S solve the problems of pollutant removal and resource recycling.
Smart Images

Figure CN119221020A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to advanced material technology and relates to an electrochemical catalyst and a preparation method thereof, specifically a bifunctional CoCu catalyst and a preparation method thereof and application in anode sulfur production and cathode ammonia production. Background Art
[0002] The large-scale discharge of sulfur and nitrates seriously threatens aquatic ecology and human health, and efficient wastewater treatment processes are urgently needed to reduce the concentration. Although traditional methods are effective, they are energy-intensive and prone to secondary pollution [Su L., Han DD, Zhu GJ, Xu H., Luo W., Wang LJ, Jiang W., Dong AG, Yang JP, Tailoring theassembly of iron nanoparticles in carbon microspheres toward high-performanceelectrocatalytic denitrification, Nano Lett. , 2019, 19, 5423-5430. Meyer D.,Prien RD, Rautmann L., Pallentin M., Waniek JJ, Schulz-Bull DE,Determination of nitrate and hydrogen sulfide in the baltic sea using anultraviolet spectrophotometer, Front. Mar. Sci. , 2018, 5, 431]. In contrast, the electrochemical method is an ideal choice because of its simple operation and no secondary pollution [Huang HY, Yu Y., Chung KH, Recovery of hydrogen and sulfur by lndirect electrolysis of hydrogen sulfide, Energy. Fuel , 2009, 23, 4420-4425.Li KT, Yen CS, Shyu NS, Mixed-metaloxide catalysts containing iron for selective oxidation of hydrogen sulfideto sulfur, Appl. Catal. A-Gen., 1997, 156, 117-130], which can convert pollutants into elemental sulfur and ammonia through redox reactions at room temperature and pressure, remove pollutants and achieve resource recovery, with significant environmental and economic benefits. Therefore, it is a reasonable and effective strategy to treat sulfur and nitrate in wastewater using electrochemical methods. The key to effectively treating these two types of pollutants using electrochemical coupling methods is to design bifunctional electrocatalysts that can simultaneously catalyze NO3RR and SOR to achieve efficient and simple treatment effects, so new catalysts need to be developed. Summary of the invention
[0003] The present invention synthesized Cu-doped CoOOH bifunctional electrocatalyst on cobalt foam (CF) by in situ growth method and used for both cathode NO3RR and anode SOR. For anode SOR, only a low potential of 0.29 V (vs. RHE) was required to achieve 100 mAcm -2 The current density of the cathode NO3RR is 96% at the optimal potential of -1.5 V (vs. RHE). Finally, the SOR is coupled with the NO3RR to drive the electrochemical reaction at a voltage of 0.3 V. The present invention provides a new idea for the degradation of dual pollutants and the recovery of high value-added products sulfur and ammonia.
[0004] The present invention adopts the following technical solution: A method for preparing a bifunctional CoCu catalyst comprises the following steps: mixing hydroxylated cobalt foam with a copper salt solution to obtain a bifunctional CoCu catalyst.
[0005] The invention discloses a method for producing ammonia from nitrate, comprising the following steps: using the above-mentioned bifunctional CoCu catalyst as a working electrode, adopting a three-electrode system, and using nitrate as a reactant to carry out an electrochemical reaction to prepare ammonia.
[0006] The invention discloses a method for producing sulfur from sulfide, comprising the following steps: using the above-mentioned bifunctional CoCu catalyst as a working electrode, adopting a three-electrode system, and using sulfide as a reactant to carry out an electrochemical reaction to prepare sulfur.
[0007] The invention discloses a method for producing sulfur and ammonia by coupling, comprising the following steps: using the above-mentioned bifunctional CoCu catalyst as a working electrode, adopting a dual electrolysis system, using nitrate as a reactant and sulfide as a reactant to carry out electrochemical reactions, and preparing ammonia and sulfur.
[0008] The present invention discloses the use of the bifunctional CoCu catalyst in the preparation of ammonia and / or sulfur. Preferably, the bifunctional CoCu catalyst is used as a working electrode to prepare ammonia and / or sulfur by an electrochemical method.
[0009] In the present invention, the cobalt foam is oxidized to prepare the hydroxylated cobalt foam; preferably, the cobalt foam is oxidized with hydrogen peroxide to prepare the hydroxylated cobalt foam.
[0010] In the present invention, in the copper salt solution, the copper salt is a water-soluble copper salt, and the solvent is water; preferably, the copper salt is a sulfate, a chloride, or the like.
[0011] In the present invention, the hydroxylated cobalt foam is mixed with a copper salt solution and reacted for 1 minute to 1 hour, preferably 10 minutes to 30 minutes, to obtain a bifunctional CoCu catalyst.
[0012] In the present invention, the hydroxylated cobalt foam is immersed in a copper salt solution to achieve mixing of the hydroxylated cobalt foam and the copper salt solution; preferably, the concentration of the copper salt solution is 0.01 M to 1 M, preferably, the concentration of the copper salt solution is 0.05 M to 0.5 M, and further preferably, the concentration of the copper salt solution is 0.1 M to 0.3 M.
[0013] In the present invention, the three-electrode system is a conventional electrochemical workstation, and the creativity of the present invention lies in using the above-mentioned bifunctional CoCu catalyst as the working electrode. In the production of ammonia from nitrate, the nitrate includes N-KNO3; in the production of sulfur from sulfide, the sulfide includes Na2S.
[0014] The present invention synthesizes Cu-doped CoOOH bifunctional electrocatalyst on cobalt foam (CF) by an in-situ growth method for both cathode NO3RR and anode SOR. For sulfur oxidation reaction, the catalyst exhibits excellent catalytic performance; in the sulfur oxidation reaction, the cobalt-based catalyst can effectively oxidize sulfur or its compounds into higher valence substances, such as sulfate, thereby achieving sulfur removal and conversion. The catalyst can effectively and stably promote the NO3RR reaction, and at the same time, the catalyst can effectively inhibit HER, thereby improving the efficiency and selectivity of the ammonia production reaction. In addition, the low cost and environmental friendliness of the catalyst also make it have great application potential in the electrochemical coupling treatment of sulfur and nitrate pollutants. Therefore, the present invention designs a bifunctional electrocatalyst that can simultaneously give play to the advantages of Cu-based and cobalt-based catalysts, which is expected to achieve efficient electrochemical coupling treatment of sulfur and nitrate. Such a bifunctional electrocatalyst will be able to catalyze NO3RR and SOR reactions simultaneously, achieving pollutant removal and resource conversion and utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 (a) SEM image of CoOOH / CF; (b) SEM image of Cu-CoOOH / CF.
[0016] Figure 2(a) TEM image of Cu-CoOOH / CF; (b) HR-TEM image of Cu-CoOOH / CF; (c) EDS element distribution map of Cu-CoOOH / CF.
[0017] Figure 3 XRD spectra of CoOOH / CF and Cu-CoOOH.
[0018] Figure 4 High-resolution XPS spectra of Cu-CoOOH: (a) full spectrum; (b) Co 2p; (c) O 1s.
[0019] Figure 5 Comparison of LSV curves of catalysts doped with different metals.
[0020] Figure 6 Evaluation of SOR performance: (a) Comparison of SOR and OER LSV curves; (b) LSV curve of SOR in 1 M NaOH + 1 MNa2S; (c) Tafel slope; (d) EIS graphs of different electrocatalysts; (e) C dl ; (f) Comparison of LSV curves before and after 5000 CV scans.
[0021] Figure 7 These are the CV curve test diagrams of different catalysts.
[0022] Figure 8 For the presence or absence of NO3 - LSV curve of Cu-CoOOH at different potentials (a); NO3RR performance of Cu-CoOOH at different potentials (b); NO3RR performance of Cu-CoOOH at different pH values (c); NO3RR performance of Cu-CoOOH at different concentrations (d).
[0023] Fig. 9 N-NO3 - , N-NO2 - and N-NH4 + Changes in yield concentration over time (a); FE and yield of NH3 under -0.6 V (vs. RHE) voltage cycling test conditions (b).
[0024] Fig.10 LSV curves of NO3RR / / OER and NO3RR / / SOR.
[0025] Fig.11 Product characterization, including (a) XRD spectrum of the product S powder (the inset is the recovered S powder product); (b) XRD spectrum of the product NH4Cl powder (the inset is the recovered NH4Cl product). DETAILED DESCRIPTION
[0026] The present invention synthesized Cu-doped CoOOH bifunctional electrocatalyst on cobalt foam (CF) by in-situ growth method and used for cathode NO3RR and anode SOR at the same time, which can efficiently electrocatalyze NO3 - Reduction to NH3 and S 2- Oxidized to S. For sulfur oxidation reactions, the catalyst exhibits excellent catalytic performance; in sulfur oxidation reactions, cobalt-based catalysts can effectively oxidize sulfur or its compounds to higher valence substances, such as sulfates, thereby achieving sulfur removal and conversion. The catalyst can promote the NO3RR reaction. At the same time, the catalyst can also effectively inhibit HER, improving the efficiency and selectivity of the ammonia production reaction. In addition, the low cost and environmental friendliness of the catalyst also make it have great application potential in the electrochemical coupling treatment of sulfur and nitrate pollutants.
[0027] The present invention discloses the use of the bifunctional CoCu catalyst in the preparation of ammonia and / or sulfur. Preferably, the bifunctional CoCu catalyst is used as a working electrode to prepare ammonia and / or sulfur by an electrochemical method.
[0028] As an example, the above-mentioned bifunctional CoCu catalyst is used as a working electrode, a three-electrode system is adopted, and nitrate is used as a reactant to carry out an electrochemical reaction to prepare ammonia.
[0029] As an example, the above-mentioned bifunctional CoCu catalyst is used as a working electrode, a three-electrode system is adopted, and sulfide is used as a reactant to carry out an electrochemical reaction to prepare sulfur.
[0030] As an example, the above-mentioned bifunctional CoCu catalyst is used as a working electrode, and a dual electrolysis system is adopted to carry out electrochemical reactions with nitrate as a reactant and sulfide as a reactant, respectively, to prepare ammonia and sulfur.
[0031] Furthermore, in the preparation of ammonia, an inert gas is introduced into the electrolyte containing NH3 obtained by the reaction for purging, and then NH3 is captured by a 1M HCl solution, and then the solvent is removed by rotary evaporation to recover the NH4Cl solid powder.
[0032] Furthermore, in the preparation of sulfur, the anode electrolyte after the reaction is collected, and then carbon dioxide gas is injected until a light yellow solid powder is precipitated and the solution becomes transparent, and then the yellow powder sulfur is collected.
[0033] The technical progress of the present invention is illustrated below through specific experiments. The raw materials involved in the present invention are existing products, and the specific preparation operations and performance tests are all conventional technologies.
[0034] Cobalt foam (CF) was purchased from Jiangsu Kunshan Green Creation Co., Ltd. The commercially available CF was ultrasonically cleaned in acetone, 3.0 M HCl, ethanol, and distilled water for 15 min in sequence to remove oil stains, oxide layers, and attached metal ions on the CF surface, and then dried with high-purity nitrogen for the following experiments. Embodiment 1
[0035] The cleaned CF was immersed in an open bottle containing a hydrogen peroxide (H2O2, 15%) solution and oxidized for 30 min. The surface of CF changed from silver to black CoOOH / CF. It was washed with ultrapure water and then dried in a vacuum oven at 60 °C for 12 h to obtain hydroxylated cobalt foam.
[0036] A piece of 2×2 cm 2 The CoOOH / CF (hydroxylated cobalt foam) was placed in 30 mL of CuSO4·5H2O (0.2 M) aqueous solution and reacted for 20 min. The black CoOOH / CF was converted into orange Cu-CoOOH / CF. The Cu-CoOOH / CF was taken out and washed with ultrapure water to obtain the final sample. The sample was dried in a vacuum oven at 60 °C for 12 h for subsequent characterization and performance testing.
[0037] The microstructure of the prepared samples was analyzed by SEM. In the SEM images, uniform vertical CoOOH nanosheet structures were observed to be in situ grown ( Figure 1 (a) The morphology of the catalyst after Cu doping was characterized, and it was found that Cu doping had a significant effect on the catalyst morphology. The smooth nanosheet structure was destroyed after Cu doping, such as Figure 1 In b, the surface of the nanosheet is irregular. TEM is used to further determine its morphology, such as Figure 2 As shown in (a), Cu-CoOOH / CF exhibits a multi-dispersed vertical nanosheet structure, which provides more active sites and promotes material transport. Figure 2 The HR-TEM results in middle b show that some areas of Cu-CoOOH present an ordered crystalline structure, which is consistent with the XRD results. Cu doping leads to the transformation of the material from a low-crystalline state to a crystalline state. The 0.43 nm lattice spacing shown in the crystalline area corresponds to the (111) crystal plane of Cu. At the same time, the EDS element mapping ( Figure 2 Figure c) shows that Cu is introduced into CoOOH, and Co, O and Cu elements are evenly distributed on the material. The crystal structures of Cu-CoOOH / CF and CoOOH / CF were analyzed by XRD characterization. Figure 3As shown, for CoOOH, its XRD spectrum has no obvious characteristic peaks, indicating that it is an amorphous structure. When Cu is doped into CoOOH to form Cu-CoOOH, obvious characteristic peaks appear in the XRD spectrum, which appear at 36.5°, 43.6°, 50.9° and 74.6°, respectively. Among them, 36.5° corresponds to the (111) plane of the CuO2 (PDF#74-1230) crystalline structure. The characteristic peaks of 43.3°, 50.4° and 74.1° match the standard card of Cu (PDF#85-1326), corresponding to the (111) (200) (220) crystal planes, respectively. This result shows that the Cu-CoOOH material has a crystalline structure. The doping of Cu significantly changes the structure of the material, from the original low crystalline state to the crystalline state. This structural transformation is due to the rearrangement and ordering of the local structure of CoOOH caused by the introduction of Cu. The composition and elemental chemical states of Cu-CoOOH / CF and CoOOH / CF samples were further investigated by XPS. Figure 4 shown. Embodiment 2
[0038] Referring to Example 1, the CuSO4·5H2O (0.2 M) aqueous solution was replaced with the FeCl3·6H2O (0.2 M) aqueous solution to obtain Fe-CoOOH / CF.
[0039] Referring to Example 1, the CuSO4·5H2O (0.2 M) aqueous solution was replaced with a NiSO4·6H2O (0.2 M) aqueous solution to obtain Ni-CoOOH / CF.
[0040] Electrochemical Experimental Examples All electrochemical performance measurements were performed using a conventional CHI 660E electrochemical station.
[0041] For the performance evaluation of SOR, the electrolyte was 1 M NaOH + 1 M Na2S with a pH of 14. A three-electrode system (Cu-CoOOH / CF as working electrode, Hg / HgO as reference electrode, and carbon rod as counter electrode) was used. The potential range was 0 to 0.5 V (vs. RHE) at 5 mV s -1 LSV curves were recorded at a scan rate of 1.5 %. Only 1 M NaOH was used as the electrolyte as a control; Fe-CoOOH / CF, Ni-CoOOH / CF, CoOOH / CF or CF were used as working electrodes for comparative experiments.
[0042] For the performance evaluation of NO3RR, a double-chamber electrolytic cell with 1 M KOH as electrolyte and 1400 ppm N-KNO3 as reactant was used, and a three-electrode system (Cu-CoOOH / CF as working electrode, Hg / HgO as reference electrode, and Pt foil as counter electrode) was adopted; the NO3RR performance test was carried out by chronoamperometry (it) under different voltages, different pH values, and different concentrations.
[0043] All LSV data are without iR correction. C is obtained from the CV curve in the non-Faraday region. dl To estimate the ECSA.
[0044] The FE of NO3RR for N-NH3 is defined as the charge generated for N-NH3 divided by the total charge passing through the working electrode during the electrolysis process. The FE and yield of NH3 are calculated as follows:
[0045]
[0046] Where F is the Faraday constant (96485.3 C mol -1 ), C N-NH3 is the concentration of N-NH3 to be measured (mol L -1 ), A is the geometric area of the electrode (cm 2 ), V is the volume of the cathode electrolyte (L), and t is the reaction time (h).
[0047] Recovery of sulfur products. After SOR, the electrolyte is collected and carbon dioxide gas is injected into the anode electrolyte after the reaction until light yellow solid powder is precipitated and the solution becomes transparent, and then the yellow powder is collected.
[0048] Recovery of ammonia product: Inert gas is introduced into the electrolyte containing NH3 for purging, and then 1 M HCl solution is used to capture NH3. The solvent is then removed by rotary evaporation to recover NH4Cl solid powder.
[0049] Example 3 Study on SOR performance of Cu-CoOOH electrode The anodic SOR performance of Cu-CoOOH / CF catalyst was studied in 1 M NaOH + 1 M Na2S solution using a conventional three-electrode system. First, the performance of different metal-doped materials was tested, such as Figure 5 As shown, the test results show that the Cu-doped catalyst exhibits the best catalytic activity.
[0050] Subsequently, the SOR performance of Cu-doped catalyst Cu-CoOOH was tested. Figure 6 In a, there is S 2- and No S 2-The LSV curves of Cu-CoOOH / CF catalysts were obtained in 1 M NaOH. In the presence of Na2S, only low potentials of 0.21 V and 0.30 V (vs. RHE) were required to achieve 50 mA cm -2 and 100 mA cm -2 The current density is higher than that of conventional OER (without S 2- ) are 1.43 and 1.41 V lower, respectively, indicating that SOR is thermodynamically more advantageous than OER.
[0051] Figure 6 The LSV curve in (b) shows that the foamed cobalt CF itself is not active for SOR. However, compared with the amorphous CoOOH / CF, Cu-CoOOH / CF has a higher SOR current density. -2 For the current density of 1.5 V, Cu-CoOOH / CF only needs a very low overpotential, which is much lower than CoOOH / CF (0.44 V), indicating that the crystalline-amorphous structure constructed by Cu doping improves the SOR activity. In order to further study the reaction kinetics of the SOR electrocatalyst, the corresponding Tafel plot was constructed based on the LSV curve. Figure 6 As shown in c, the minimum Tafel slope of Cu-CoOOH / CF is 109.14 mV dec -1 , which is significantly lower than CoOOH / CF (153.58 mV dec -1 ) and CF (186.51 mV dec -1 ), indicating that the SOR kinetics of Cu-CoOOH / CFP is more favorable. This result is due to the Cu incorporation, which introduces a more favorable electronic structure and leads to the exposure of more active sites.
[0052] In order to further reveal the promoting effect of Cu doping on SOR performance, the EIS and ECSA of the catalysts were evaluated. Figure 6 As shown in Figure d, the EIS graphs of CoOOH / CF and Cu-CoOOH / CF were obtained. The semicircular diameter at high frequency corresponds to the charge transfer resistance (R ct ), R ct The value is smaller than that of CoOOH / CF and CF, indicating that Cu-CoOOH / CF has good charge transfer kinetics, which is conducive to the efficient charge transfer of SOR. Figure 7 ) The relationship between current density and scan rate is obtained by dl Value. Figure 6 As shown in Figure e, the calculated Cu-CoOOH / CF (51.58 mF cm -2) is higher than CoOOH / CF (40.67 mF cm -2 ) and CF (27.49 mF cm -2 ), indicating that Cu-CoOOH / CF has a larger ECSA and is therefore more likely to expose electrochemically active sites for sulfur oxidation. Figure 6 As shown in (f), even after 5000 consecutive CV cycles, the polarization curve shows a negligible decrease compared with the first cycle curve, indicating that Cu-CoOOH / CF has good stability.
[0053] After SOR, the electrolyte was collected, and carbon dioxide gas was injected into the anode electrolyte after the reaction until light yellow solid powder was precipitated and the solution became transparent, and then yellow powdered sulfur powder was collected.
[0054] Example 4 Study on NO3RR Performance of Cu-CoOOH Electrode In the presence of 0.1 M NO3 - The cathode NO3RR performance of Cu-CoOOH / CF was studied in a H-type electrolytic cell using a conventional three-electrode system in 1 M KOH solution. Figure 8 The Cu-CoOOH / CF shown in a was dissolved in 1 M KOH solution and 0.1 M NO3 - LSV curve in solution. In 0.1 M NO3 - In the presence of Cu-CoOOH / CF, a significant increase in current density can be observed, indicating that Cu-CoOOH / CF has a strong affinity for NO3 - Based on the analysis of LSV, a series of constant potential tests were carried out at different voltages to further accurately evaluate the ammonia yield of Cu-CoOOH / CF and the NO3RR performance of FE. Figure 8 As shown in Figure b, in the voltage range from -0.4 V to -0.8 V (vs. RHE), the ammonia yield shows an upward trend, while the Faradaic efficiency first increases and then decreases. At a voltage of -0.6 V (vs. RHE), the maximum Faradaic efficiency of ammonia reaches 96%, and the corresponding ammonia yield is 62.03 mg h -1 cm -2 Under different pH conditions (adjusted by dripping hydrochloric acid), the Faradaic efficiency of ammonia did not fluctuate significantly and remained at around 96%, which shows that the Cu-CoOOH / CF material has a wide range of applicability for NO3RR ( Figure 8 c). Whether in acidic, neutral or alkaline environments, the material can maintain relatively stable performance and effectively reduce nitrate to ammonia. Figure 8 As shown in Figure d, when NO3 -As the concentration increases, the Faradaic efficiency of ammonia increases first and then tends to stabilize, which indicates that the Cu-CoOOH / CF material has a high tolerance to the nitrate concentration of NO3RR.
[0055] An inert gas is introduced into the electrolyte containing NH3 for purging, and then NH3 is captured by a 1 M HCl solution, and then the solvent is removed by rotary evaporation to recover the NH4Cl solid powder.
[0056] like Fig. 9 As shown in (a), during the 10 h NO3RR electrolysis of Cu-CoOOH / CF at -0.6 V (vs. RHE), the N-NO3 - The concentration can be continuously reduced to N-NH4 + , during the whole NO3RR electrolysis process, NO3 - -NH4 + The conversion rate exceeded 95%, confirming the excellent NO3RR selectivity of Cu-CoOOH / CF. After 10 cycles, there was no significant attenuation of ammonia yield and FE ( Fig. 9 (b) demonstrates high catalytic stability. The electrolyte was replaced once an hour, and 10 hours represents 10 cycles.
[0057] Example 5 Study on SOR / / NO3RR coupling performance In view of the electrocatalytic performance of Cu-CoOOH / CF cathode NO3RR and anode SOR, the dual-electrode coupling system assembled using Cu-CoOOH / CF bifunctional catalyst as cathode and anode can maximize the energy efficiency and produce targeted high-value-added chemicals at the cathode and anode.
[0058] All electrochemical performance measurements were performed using a conventional CHI 660E electrochemical station and a dual-chamber electrolytic cell. The electrolyte in the anode compartment was 1 M NaOH + 1 M Na2S, and the electrolyte in the cathode compartment was 1 M KOH + 1400 ppm N-KNO3; a two-electrode system (Cu-CoOOH / CF was fixed with a platinum electrode clamp as the anode and cathode) was used. The potential range was 0-0.5 V (vs. RHE) at 5 mV s -1 LSV curves were recorded at a scan rate of 1.3 s. All LSV data were without iR correction. As a control, Na2S was omitted from the water splitting system, and the rest was the same.
[0059] Fig.10 The LSV curves of the dual-electrode coupling system and the water splitting system are shown, among which the former shows obvious advantages. -2At a current density of 1.5 V, the cell voltage of 0.3 V is 1.5 V lower than that of conventional water splitting (1.8 V), which means a significant reduction in the energy consumption of electrolysis.
[0060] The generated sulfur was extracted by injecting carbon dioxide gas into the electrolyte until the pale yellow solid powder precipitation solution became transparent, and then the yellow powder was collected and determined to be elemental sulfur (S8, PDF#08-0247) by XRD measurement ( Fig.11 In a). Inert gas is introduced into the electrolyte containing NH3 for purging, and then 1 M HCl solution is used to capture NH3 to recover NH4Cl product. Fig.11 As shown in Figure b, the recovered NH4Cl product highly matches the characteristic peak of the XRD standard card (PDF#73-0365). This result proves the successful recovery of elemental sulfur and ammonium chloride.
[0061] summary The present invention synthesized Cu-doped CoOOH (Cu-CoOOH / CF) bifunctional catalyst electrode on the surface of CF by in-situ self-growth method for efficient electrocatalysis of NO3 - Reduction to NH3 and S 2- The optimized catalyst Cu-CoOOH / CF exhibited excellent SOR performance at 100 mA cm -2 At a current density of -0.60 V (vs. RHE), only a low voltage of 0.30 V (vs. RHE) is required. In addition, the material also has excellent NO3RR performance. At a voltage of -0.60 V (vs. RHE), the maximum Faraday efficiency of ammonia reaches 96%, and the corresponding ammonia yield is 62.03 mg h -1 cm -2 Finally, the NO3RR / / SOR coupling reaction was designed to convert the two pollutants (NO3 - and S 2- ) is converted into value-added products (NH3 and S) with low energy consumption, and the solid product NH4Cl is successfully extracted, realizing the effective recovery and utilization of pollutants. In addition, the elemental sulfur extraction method is further optimized, and the sulfur separation method using carbon dioxide is efficient, environmentally friendly, and cost-effective. The present invention uses in-situ characterization technology to monitor in real time the structural changes of the catalyst and the generation of intermediates during the NO3RR and SOR reactions, thereby revealing the nature of the catalytic reaction. This study provides a new idea for the degradation of dual pollutants and the recovery of high value-added products sulfur and ammonia.
Claims
1. A method for preparing a bifunctional CoCu catalyst comprises the following steps: mixing hydroxylated cobalt foam with a copper salt solution to obtain a bifunctional CoCu catalyst.
2. The method for preparing the bifunctional CoCu catalyst according to claim 1, characterized in that: The cobalt foam is oxidized to prepare the hydroxylated cobalt foam.
3. The method for preparing the bifunctional CoCu catalyst according to claim 1, characterized in that: In the copper salt solution, the copper salt is a water-soluble copper salt; the concentration of the copper salt solution is 0.01 M to 1 M.
4. The method for preparing the bifunctional CoCu catalyst according to claim 1, characterized in that: The hydroxylated cobalt foam is mixed with a copper salt solution and reacted for 1 minute to 1 hour to obtain a bifunctional CoCu catalyst.
5. A bifunctional CoCu catalyst prepared according to the method for preparing a bifunctional CoCu catalyst according to claim 1.
6. A method for producing ammonia from nitrate, comprising the following steps: using the bifunctional CoCu catalyst according to claim 5 as a working electrode, adopting a three-electrode system, and using nitrate as a reactant to carry out an electrochemical reaction to prepare ammonia.
7. A method for producing sulfur from sulfide, comprising the following steps: using the bifunctional CoCu catalyst according to claim 5 as a working electrode, adopting a three-electrode system, and using sulfide as a reactant to carry out an electrochemical reaction to prepare sulfur.
8. A method for producing sulfur and ammonia by coupling, comprising the following steps: using the bifunctional CoCu catalyst according to claim 5 as a working electrode, adopting a dual electrolysis system, using nitrate as a reactant and sulfide as a reactant to carry out electrochemical reactions to prepare ammonia and sulfur.
9. An electrochemical workstation, characterized in that: The bifunctional CoCu catalyst according to claim 5 is used as the working electrode.
10. Use of the bifunctional CoCu catalyst according to claim 5 in the preparation of ammonia and / or sulfur.
Citation Information
Cited By
Copper-phosphorus / foam cobalt composite catalyst and preparation method and application thereof
CN119877023A
Bifunctional catalyst as well as preparation method and application thereof
CN121669216A
A bifunctional catalyst, its preparation method and use
CN121669216B